Biological value (in vitro and in sacco) of chemically treated feather as rumen by pass protein source - W Puastuti; D Yulistiani; I-W Mathius (Indonesian Center for Animal Research and Development (ICARD), 2004)
A series of experiments has been conducted to study chemical processing method of feather meal using hydrocloric acid (HCl) and to evaluate the biological values by in vitro and is sacco methods of the hydrolitic feather meal (HBA). Feather meal was hydrolyzed using four levels of HCl concentration (i.e.0, 6, 12 and 24%) in three incubation times (i.e. 2, 4, and 6 days). The hydrolysis reaction was carried out in closed container in the ratio of feather meal and HCl of 2:1 (w/v). In vitro evaluation was conducted to measure dry matter (DM) and organic matter (OM) digestibility, DM solubility, ammonia (NH3) and volatile fatty acid (VFA) content. In sacco to observe the degradation of HBA crude protein. Results of in sacco evaluation in rumen showed that soluble and degraded crude proteins (CP) were significantly only affected by HCl concentration (P<0.01). The rate and the amount of degraded protein in 24 hours inclution in the rumen were affected by the HCl concentration and incubation time of hydrolysis. More amino acid degradation occurred on longer time showed that HCl had quadratic effect (P<0,01) on pH of HBA. However durations of hydrolysis did not significantly affect acidity (P>0.05). In vitro DM and OM digestibilities of HBA increased as the concentration of HCl was increased. The increase of DM digestibility followed the equation Y = -0.0231x3 + 0.7323x2 – 1.5716x + 12.383 (r = 0.994); and the OM digestibility followed the equation Y = -0.0229x3 + 0.7194x2 – 1.0606x + 15.951 (r = 0.993). Time of incubation, on the other hand, did not affect OM and DM digestibilities (P>0.05). DM solubility of HBA was significantly affected by HCl concentration and the length of incubation time (P<0.01). The increase of DM solubility was followed by the increase of NH3 content (P<0.01). The relation between DM solubility and NH3 content followed the equation Y = 0.4365x + 5.4047 (r = 0.966). The increase of DM solubility followed the equation Y = -0.027x3 + 0.9596x2 – 4.8142x + 5.3878 (r = 0.973) and the increase of NH3 content followed the equation Y = -0.0085x3 + 0.3175x2 – 1.4139x + 7.0889 (r = 0.992). Result of in sacco evaluation showed that fraction of crude protein (CP) disolved and fraction of CP degraded in rumen was significantly affected by HCl concentration (P<0.01), while the rate of CP degradation and the amount of fraction degraded during 24 hours in the rumen were affected by the HCl concentration and the durations of hydrolysis (P<0.01) indicating that more feather meal protein was hydrolized by HCl, therefore weakened or cut the chain of amino acid in the feather protein. Treatment with 12% HCl for 4 days hydrolysis of feather meal resulted in CP fraction degradation during 24 hours incubation in the rumen of 53%, indicating that the potency of CP of HBA as rumen by pass protein was 47%. Key words: Chicken feather, HCl hydrolysis, digestibility by pass protein